Heart lamp : selected stories - Mushtaq, Banu (Penguin Random House India Pvt. Ltd., 2025)
In the twelve stories of 'Heart Lamp', Banu Mushtaq exquisitely captures the everyday lives of women and girls in Muslim communities in southern India. Published originally in the Kannada language between 1990 and 2023, praised for their dry and gentle humour, these portraits of family and community tensions have garnered both censure from conservative quarters as well India's most prestigious literary awards.